PERANCANGAN SISTEM PHARFACILLE BERBASIS WEBSITE DENGAN METODE AGILE - Septa Malan Vergantana (Institut Teknologi dan Kesehatan Bintang Persada, 2026)
This research designed a web-based pharmacy information system named PHARFACILLE to resolve the problems of delayed report generation, stock recording errors, and inefficient customer service caused by the use of manual systems. The approach applied in this study involved qualitative research methods and software development utilizing the Agile method. The system design was systematically outlined using standard modeling language through the evaluation of functional modules in stages. The results indicated that the developed system successfully integrated cashier transactions, prescription records, drug stock management, inventory ordering, and financial reporting. The utilization of this system improved operational data accuracy, accelerated the service process, and reduced the dependency on manual recording. The designed system effectively facilitated the transformation of pharmacy management into a modern, transparent, and accountable digital environment.